Fiber feather-shaped nanocrystalline bismuth telluride thermoelectric thin film with high toughness and preparation method of fiber feather-shaped nanocrystalline bismuth telluride thermoelectric thin film

By adjusting the sputtering parameters at room temperature, a high-tough fiber feather-like nanocrystalline bismuth telluride thermoelectric film was grown, which solved the problems of poor flexibility and insufficient thermoelectric performance of the existing thermoelectric film, and achieved a coordinated improvement of high toughness and excellent thermoelectric performance.

CN119663178AActive Publication Date: 2025-03-21WUHAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411767901.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing thermoelectric films have fewer bending times under large deformations, poor flexibility, and low in-crystal defect density, so they cannot coordinately adjust the electrical conductivity and thermal conductivity to improve thermoelectric performance.

Method used

At room temperature, by changing the total sputtering time and sputtering bias voltage, the film thickness, grain size and internal grain defects are controlled, and a nanocrystalline bismuth telluride thermoelectric film with high toughness is grown.

Benefits of technology

The high toughness and excellent thermoelectric properties of the bismuth telluride thermoelectric film are achieved, and the resistivity can be maintained at high bending times, and the high conductivity is maintained while reducing the thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663178A_ABST
    Figure CN119663178A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and particularly relates to a fiber feather-shaped nanocrystalline bismuth telluride thermoelectric thin film with high toughness and a preparation method thereof. The method comprises the following steps: (1) taking a silicon oxide wafer and polyimide as a substrate, fixing the substrate to a basal disc, and putting the basal disc into a sputtering cavity; (2) fixing the tellurium bismuth alloy target on a direct-current power supply, fixing the tellurium elementary substance target on a radio-frequency power supply, adjusting the distance among the tellurium bismuth alloy target, the tellurium elementary substance target and the substrate, closing a cabin door, and cleaning the substrate by utilizing an ionization method; and (3) after the cleaning is finished, growing the fiber feather-shaped nanocrystalline bismuth telluride thermoelectric thin film with high toughness by adopting an intermittent sputtering method. According to the method, the high-toughness fiber feather-shaped nanocrystalline bismuth telluride thermoelectric thin film is grown in one step by adjusting the total sputtering time and the sputtering bias voltage at the room temperature and under the fixed working air pressure for the first time, the requirements of flexible wearable thermoelectric devices can be met, and the method has potential commercial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoelectric materials, and in particular relates to a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness and a preparation method thereof. Background Art

[0002] With the flexible development of wearable devices in daily life and biomedicine, traditional rigid semiconductors cannot meet the growing demand for wearables. Thermoelectric materials can convert heat into electrical energy. At the same time, flexible thermoelectric materials can be in close contact with the human body, maximizing the energy conversion efficiency. Powering wearable devices through human body heat has become a research direction with great application prospects. In the research of thermoelectric materials, bismuth telluride materials are of great significance to the commercialization of thermoelectric devices due to their excellent thermoelectric properties. However, compared with the continuous development of the thermoelectric properties of bismuth telluride-based films, the research on its mechanical properties is seriously lagging behind, and the lack of mechanical strength and toughness limits its further commercial application. Studies on related films have found that the shape, size and distribution of grains, as well as the type and density of defects contained in the grains, have a significant impact on the mechanical, thermal and electrical properties of the film. Related studies have found that when the film grain size is gradient distributed and there are more stacking faults inside the grains, the strength and toughness of the material can be synergistically improved due to the hindering effects of grain boundaries and stacking faults on crack propagation and dislocation slip, respectively.

[0003] In the prior art, document 1 (Jin Q, Jiang S, Zhao Y, et al. Flexible layer-structured Bi2Te3 thermoelectric on a carbon nanotube scaffold [J]. Nature Materials, 2018, 18 (1): 62-68.) reported a (000l) oriented bismuth telluride film deposited on a carbon nanotube by magnetron sputtering, with an operating pressure of 0.5 Pa and an operating temperature of 650 K. The film was cyclically bent 100 times at a bending radius of 10 mm without significant loss.

[0004] Reference 2 (Zheng ZH, Shi XL, Ao DW, et al. Harvesting waste heat with flexible Bi2Te3 thermoelectric thin film [J]. Nature Sustainability, 2022, 6 (2): 180-191.) reported that Ag / Bi and Te were first deposited on a polyimide substrate, respectively, with a working pressure of 1 Pa. Then, the two were placed in a vacuum furnace and 5 N mm -2External pressure made them in close contact and heat treated at 350℃ for 30min. The obtained film was bent 2000 times at a bending radius of 18mm, and the resistivity increased by 10%.

[0005] Reference 3 (Karthikeyan V, Surjadi JU, Li X, et al. Three dimensional architected thermoelectric devices with high toughness and power conversion efficiency [J]. Nature Communications, 2023, 14 (1): 2069.) reported that bismuth telluride thin films were deposited by thermal evaporation at room temperature and heat treated at 220 ° C. The maximum Seebeck coefficient of the obtained film at 350 K was 187 μVK -1 The conductivity reaches a maximum value of 435Scm at 550K -1 , the power factor is always stable at 6μWcm -1 K -2 nearby.

[0006] Reference 4 (Lu Y, Zhou Y, Wang W, et al. Staggered-layer-boosted flexible Bi2Te3 films with high thermoelectric performance [J]. Nature Nanotechnology, 2023, 18 (11): 1281-1288.) reported that Bi was first prepared by zone melting method and Bridgman method respectively. 0.5 Sb 1.5 Te3and Bi2Te 2.7 Se 0.3 The single crystal was then cut along the (000l) cleavage plane and peeled off with transparent adhesive to obtain p-type and n-type bismuth telluride thin films. The film was cyclically bent 1000 times at a bending radius of 4 mm, and the conductivity decayed by 9%.

[0007] Literature 5 (Zheng ZH, Zhong YM, Li YL, et al. Ultrahigh thermoelectric properties of p-type Bi x Sb 2-xTe3 thin films with exceptional flexibility for wearable energy harvesting[J].Carbon Energy,2024,6(8):22276-22285.) reported that Bi / Sb and Te were first deposited on different polyimide substrates by thermal evaporation, with evaporation powers of 14 W and 10 W, respectively, and working pressure of 2×10 -3 Pa, and then heated at 350 ° C for 30 min to prepare Bi x Sb 2-x Te3 film. The resistivity of the film increased by 5% after 1000 cycles of bending at a bending radius of 5 mm.

[0008] Document 6 (CN 106498354 A A method for preparing a bismuth telluride thermoelectric film with a hexagonal spiral morphology, 2017.) proposes a method for preparing a bismuth telluride thermoelectric film with a hexagonal spiral morphology. First, a target material is installed and a quartz glass substrate is fixed on a base; the distance between the target material and the quartz glass substrate is adjusted and evacuated to a specified standard; the quartz glass substrate is heated to 300°C to 400°C, and a film is prepared by co-sputtering under a working gas pressure of 0.3Pa to 0.5Pa; finally, the sputtered film is annealed at 250°C to 350°C to form a bismuth telluride thermoelectric film with a hexagonal spiral morphology.

[0009] Document 7 (CN 108447976 A A method for regulating the performance of n-type bismuth telluride film by grain boundaries, 2018.) proposes a method for regulating the performance of n-type bismuth telluride film by grain boundaries, the method comprising the following processes: the first step is to prepare an n-type Bi2Te3 film on a heated substrate by magnetron sputtering technology, the second step is to plate Sn on the surface of the n-type Bi2Te3 film by thermal evaporation technology, and the third step is to anneal the Sn-plated n-type Bi2Te3 at high temperature in a protective gas annealing furnace and cool it with the furnace to obtain a high-performance n-type Bi2Te3 film.

[0010] Document 8 (CN 109554674 A A method for preparing a bismuth telluride thermoelectric film with a heterostructure, 2019.) proposes a method for preparing a bismuth telluride thermoelectric film with a heterostructure. First, a target material is installed and a magnesium oxide (MgO) single crystal is fixed on a substrate table; the distance between the target material and the quartz glass substrate is adjusted and vacuumed to a specified standard; the magnesium oxide (MgO) substrate is heated to 320°C to 400°C, and a thin film is prepared by co-sputtering under a working gas pressure of 1Pa to 3Pa; finally, the sputtered film is annealed at 350°C to 450°C to form a bismuth telluride thermoelectric film with a heterostructure.

[0011] Document 9 (CN 115595542 A A superhard nano-heterogeneous medium-entropy alloy film and preparation method thereof, 2022.) discloses a superhard nano-heterogeneous medium-entropy alloy film and a preparation method thereof, wherein the superhard nano-heterogeneous CrCoNi alloy is a nanocrystalline composite material composed of short columnar crystals and equiaxed crystals dispersed around the columnar crystals, and the heterogeneous structure here is prepared by spaced sputtering. These dispersed equiaxed crystals improve the anisotropic mechanical behavior of the medium / high entropy alloy columnar nanostructures previously prepared by magnetron sputtering.

[0012] Most of the preparation methods of thermoelectric films in the prior art need to be prepared at high temperature (at least 220°C), and the preparation process needs to be carried out in multiple steps, which limits the large-scale production in the industrial field. The prepared films are all columnar, hexagonal spiral and hexagonal nanocrystals of a single size, which cannot break the constraint relationship between the nanocrystal and flexibility of the material, have few bending times under large deformation, and have poor flexibility of the film. In addition, the intracrystalline defect density is low, and it is impossible to achieve synergistic regulation of electrical conductivity and thermal conductivity to improve the thermoelectric properties of the film. Therefore, how to prepare a bismuth telluride film with a new structure, excellent mechanical properties and thermoelectric properties in one step at room temperature is of great significance for the development of high-performance flexible wearable thermoelectric devices. Summary of the invention

[0013] The purpose of the present invention is to provide a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness and a preparation method thereof. The present invention grows a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness by changing the total sputtering time and the sputtering bias voltage to control the film thickness, grain size and internal defects of the grains under room temperature conditions and fixed working pressure.

[0014] The implementation process of the present invention is as follows:

[0015] A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness comprises the following steps:

[0016] (1) Using a silicon oxide wafer and polyimide as a substrate, fixing the substrate to a base plate and then placing it into a sputtering chamber;

[0017] (2) fixing the tellurium-bismuth alloy target on a direct current power supply, fixing the tellurium target on a radio frequency power supply, adjusting the distances between the tellurium-bismuth alloy target, the tellurium target and the substrate, and cleaning the substrate by an ionization method;

[0018] (3) After cleaning, an intermittent sputtering method is used to grow a fibrous feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness.

[0019] Furthermore, in step (1), the pretreatment process of the silicon oxide wafer and the polyimide is to select a single-sided polished silicon oxide wafer and polyimide as a substrate, immerse them in water and alcohol, and then clean them with an ultrasonic cleaner, and dry the substrate surface after cleaning.

[0020] Furthermore, in step (2), the process of cleaning the substrate by ionization method is to introduce argon gas under vacuum conditions, apply sputtering bias, set the pulse duty cycle, close the hatch, and use ionized argon ions to clean the substrate.

[0021] Furthermore, in step (3), the intermittent sputtering method is to set the parameters of argon gas flow rate, working gas pressure, substrate speed, sputtering temperature, RF power supply power, DC power supply power, sputtering bias, and pulse duty cycle, and then sputter for 12 to 17 minutes for the first time, and then turn off the RF and DC power supplies for 10 to 30 minutes after the sputtering is completed. The second sputtering is 12 to 17 minutes, and then turn off the RF and DC power supplies for 10 to 30 minutes after the sputtering is completed, and so on, and the sputtering process is repeated a total of 3 to 5 times.

[0022] Furthermore, in step (3), after the intermittent sputtering is completed, the RF and DC power supplies are turned off, and after maintaining the vacuum condition for 1 to 2 hours, a fibrous feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness is obtained.

[0023] Furthermore, in step (2), the distance between the tellurium-bismuth alloy target, the tellurium target and the substrate is 95 to 105 mm. Preferably, the purity of the tellurium-bismuth alloy target and the tellurium target is ≥ 99.9%, the atomic ratio of Bi to Te in the tellurium-bismuth alloy target is 2:3, the size of the tellurium-bismuth alloy target and the tellurium target is Φ74.2×4 mm, and the size of the backing plate is Φ76.2×4 mm.

[0024] Furthermore, in the process of cleaning the substrate by the ionization method, the vacuum degree of the vacuum condition is 1×10 - 4 Pa~5×10 -4 Pa; the sputtering bias voltage is 750-850V; the pulse duty cycle is set to 50%-80%.

[0025] Furthermore, in the intermittent sputtering method, the argon gas flow rate is set to 85-90 sccm, the working gas pressure is fixed to 2-3 Pa, the substrate rotation speed is set to 10-20 rpm, the sputtering temperature is set to 20-30°C, the RF power supply power is set to 38-42 W, the DC power supply power is set to 8-12 W, the sputtering bias is set to 0-150 V, and the pulse duty cycle is set to 50%-80%.

[0026] Furthermore, in step (1), the substrate is fixed to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then loaded into the sputtering chamber, with the silicon oxide wafer in the center and the polyimide around it. The silicon oxide wafer substrate and the polyimide substrate are on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 2 to 5 mm.

[0027] A fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness is prepared by the above-mentioned preparation method.

[0028] Positive effects of the present invention:

[0029] (1) In terms of preparation method, the present invention innovatively grows a high-toughness fiber-feather-like nanocrystalline bismuth telluride thermoelectric film in one step by adjusting the total sputtering time and sputtering bias voltage under room temperature and fixed working gas pressure.

[0030] (2) In terms of mechanical properties, compared with traditional single-sized columnar grains, the feather-shaped nanocrystalline bismuth telluride thermoelectric film prepared by the present invention is composed of agglomerates of numerous nanocrystals and has a grain size gradient distribution from bottom to top, which synergistically enhances the strength and toughness of the bismuth telluride thermoelectric film.

[0031] (3) In terms of thermoelectric performance, the feather-like nanocrystalline bismuth telluride thermoelectric film prepared by the present invention is composed of more grains of different sizes compared to traditional tiny columnar crystals, and has high-density fibrous stacking faults grown inside. It can avoid significant blocking of electrons while scattering phonons, maintain high electrical conductivity while reducing thermal conductivity, and achieve improved thermoelectric performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The following are photos of the instruments used in the preparation method of the present invention;

[0033] Figure 2 This is a photo of a silicon oxide wafer and a polyimide substrate of an apparatus used in the preparation method of the present invention after being fixed on a base plate;

[0034] Figure 3 The X-ray diffraction patterns of Example 1-2 and Comparative Example 1-2;

[0035] Figure 4 This is a scanning electron microscope image of Example 2;

[0036] Figure 5 are low-magnification transmission electron microscope images of Example 1 and Example 3, wherein a is an image of Example 1 under dark field, b is a local enlarged view of a, c is an image of Example 3 under dark field, and d is a schematic diagram of a fibrous feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness;

[0037] Figure 6 This is a high-power transmission electron microscope image of Example 3;

[0038] Figure 7 It is a statistical picture of the grain size of Examples 1-2 and Comparative Example 1;

[0039] Figure 8 It is a statistical picture of the critical strain of uniaxial tensile crack of Example 1-2 and Comparative Example 1-2;

[0040] Fig. 9 The bending pictures of Examples 1-2 and Comparative Example 1, wherein a is a real-life image of the bending device, b is a finite element simulation diagram of the bending process, c is a diagram of resistance change during the bending cycle, and d is a partial enlarged diagram of c;

[0041] Fig.10 The surface scanning electron microscope images of Example 1 before and after bending 3000 times, wherein a is the image of Example 1 before bending, and b is the image after bending 3000 times;

[0042] Fig.11 The graphs are the relationship between the conductivity (σ) and the temperature (T) of Example 1 and Comparative Example 1;

[0043] Fig.12 The figure is a graph showing the relationship between the power factor (PF) and the temperature (T) of Example 1;

[0044] Fig.13 Schematic diagram of electron transport and phonon scattering in a high-tenacity fiber-feather-like nanocrystalline bismuth telluride thermoelectric film;

[0045] Fig.14 This is a picture of Example 1 using body temperature to generate electricity after bending 3000 times, where a is a schematic diagram of the power generation device and b is a picture of voltage changing with time. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the embodiments.

[0047] The present invention utilizes magnetron sputtering technology, selects a tellurium bismuth alloy target and a tellurium single target for co-sputtering at room temperature and fixed gas pressure, and controls parameters such as the total sputtering time and sputtering bias voltage to grow a high-toughness fiber-feather-like nanocrystalline bismuth telluride thermoelectric film using an intermittent sputtering method.

[0048] In the present invention, "feather-like" refers to a large number of nanocrystals with gradient sizes agglomerated together to form feather-shaped nanocrystals. "Fiber" refers to the strip-shaped stacking faults inside the grains. Applying a bias voltage can repel positively charged sputtering source ions, resulting in a reduction in ion bombardment of the substrate, thereby reducing the sputtering rate. In addition, when a positive bias is applied, the substrate will attract negatively charged electrons. The aggregation of electrons may affect the local plasma density, reduce the activity of the plasma, and cause the sputtering efficiency to further decrease, thereby controlling the thickness of the grown bismuth telluride thermoelectric film. Adjusting the total sputtering time can also adjust the film thickness. The film thickness is positively correlated with the grain size, that is, the greater the film thickness, the larger the grain size, and the more defects (such as dislocations and stacking faults) that can be accommodated inside the grain.

[0049] The feather-like nanocrystalline bismuth telluride thermoelectric film prepared by the present invention is agglomerated by numerous nanocrystals, and has a grain size with a gradient distribution from bottom to top, so that the strength and toughness of the bismuth telluride thermoelectric film are synergistically enhanced. The small grains below the feather-like nanocrystals can provide strength, and the large grains above provide the ability of plastic deformation, thereby achieving a synergistic improvement of strong plasticity. Dislocations, as the main carrier of the slip process in the crystal, represent the ability of the crystal to plastically deform. As the grain size increases, the number of dislocations and the slippable area increase, and the plastic deformation ability of the material increases accordingly. In addition, fibrous stacking faults can be regarded as "obstacles" in the dislocation movement path, and dislocations need to overcome additional energy to continue to slip. When encountering stacking faults, dislocations need to overcome greater energy barriers, thereby requiring higher external stress to promote the continued movement of dislocations. This process actually increases the friction between the slip layers, so that the material exhibits higher strength. At the same time, stacking faults further hinder the relative movement of the slip layer by constraining the slip layer, so that the material absorbs more energy during the deformation process and exhibits a better toughening effect. By hindering dislocation motion, stacking faults increase the energy dissipation inside the grains, thereby synergistically improving the strength and toughness of the material.

[0050] ZT value is an important indicator to measure the thermoelectric performance of materials. 2σT / κ. Wherein S, σ, κ and T represent Seebeck coefficient, electrical conductivity, thermal conductivity and absolute temperature, respectively. Wherein the size of electrical conductivity σ and thermal conductivity κ are determined by electron and phonon transport, respectively, so electron and phonon transport and coupling determine the final thermoelectric properties of the material. Compared with the traditional tiny columnar crystals, the feathery nanocrystalline bismuth telluride thermoelectric film prepared by the present invention is composed of more grains of different sizes, and a high-density fibrous stacking fault grows inside. Since the wavelength of phonons is often longer than that of electrons, especially low-frequency phonons, a higher number of grain boundaries and high-density stacking faults inside the grains can effectively scatter low-frequency phonons, resulting in a decrease in thermal conductivity. At the same time, grain boundaries and stacking faults do not significantly block electrons with shorter wavelengths, that is, they do not scatter high-frequency electrons, so that the electrical conductivity remains at a high level. Therefore, the structure prepared by the present invention can avoid significant blocking of electrons while scattering phonons, maintain high electrical conductivity while reducing thermal conductivity, and achieve an improvement in the thermoelectric properties of the material.

[0051] The instrument used in the method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness of the present invention is a high vacuum multi-target magnetron sputtering coating system, the manufacturer is Beijing Techno Technology Co., Ltd., the model is JCP500, see Figure 1 The photo of the silicon oxide wafer and the polyimide substrate fixed on the base is shown in Figure 2 .

[0052] A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness comprises the following steps:

[0053] (1) Selecting single-side polished silicon oxide wafers and polyimide as substrates, immersing them in water and alcohol and cleaning them with an ultrasonic cleaning machine at least 3 times, each time for 3 minutes to 5 minutes, and changing the water and alcohol before each cleaning. After cleaning, drying the substrate surface at 50 to 70° C., fixing the substrate to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then loading it into the sputtering chamber, with the silicon oxide wafer at the center and the polyimide around, the silicon oxide wafer substrate and the polyimide substrate on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 2 to 5 mm;

[0054] (2) Fix the tellurium-bismuth alloy target on a DC power supply, fix the tellurium target on a radio frequency power supply, and adjust the distance between the tellurium-bismuth alloy target, the tellurium target, and the substrate to 95-105 mm. Close the hatch, and wait for the mechanical pump and molecular pump to pump the vacuum in the chamber to 1×10 -4 Pa~5×10 -4 After Pa, high-purity argon gas with a purity of ≥99.999% is introduced, and a sputtering bias voltage of 750-850V is applied, and the pulse duty cycle is set to 50%-80%, and the substrate is cleaned for 5-10 minutes using the ionized argon ions;

[0055] (3) After the cleaning is completed, the argon flow rate is set to 85-90sccm, the working gas pressure is fixed to 2-3Pa, the substrate rotation speed is set to 10-20rpm, the sputtering temperature is set to 20-30°C, the RF power supply power is set to 38-42W, the DC power supply power is set to 8-12W, the sputtering bias is set to 0-150V, and the pulse duty cycle is set to 50%-80%. The first sputtering is 12-17 minutes. After the sputtering is completed, the RF and DC power supplies are turned off for 10-30 minutes. The second sputtering is 12-17 minutes. After the sputtering is completed, the RF and DC power supplies are turned off for 10-30 minutes. And so on. The sputtering process is repeated 3-5 times in total. The film is grown by an intermittent sputtering method. After the intermittent sputtering is completed, the RF and DC power supplies are turned off. After maintaining under vacuum conditions for 1-2 hours, a fiber-feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness is obtained.

[0056] The drying temperature of the single-sided polished silicon oxide wafer and polyimide substrate after cleaning in the present invention is 50-70°C. The purity of the tellurium bismuth alloy target and the tellurium single target in the present invention are both ≥99.9%, the atomic ratio of Bi and Te in the tellurium bismuth alloy target is 2:3, the size of the tellurium bismuth alloy target and the tellurium single target are both Φ74.2×4mm, and the size of the back plate is both Φ76.2×4mm. In addition, tellurium bismuth alloy targets and tellurium single targets with other parameters can also be selected as long as the effect of the present invention can be achieved. The argon gas in the present invention is high-purity argon gas with a purity of ≥99.999%. In the pretreatment process of the silicon oxide wafer and polyimide in the present invention, ultrasonic cleaning is performed at least 3 times, each time for 3-5 minutes, and water and alcohol need to be replaced before each cleaning.

[0057] Example 1

[0058] A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness comprises the following steps:

[0059] (1) Selecting single-side polished silicon oxide wafers and polyimide as substrates, immersing them in water and alcohol and cleaning them with an ultrasonic cleaning machine for 3 times, each time for 4 minutes, and replacing water and alcohol before each cleaning. After cleaning, drying the substrate surface at 70° C., fixing the substrate to a base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then loading it into a sputtering chamber, with the silicon oxide wafer at the center and the polyimide around, the silicon oxide wafer substrate and the polyimide substrate on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 4 mm;

[0060] (2) Fix the tellurium-bismuth alloy target on a DC power supply, fix the tellurium target on an RF power supply, and adjust the distance between the tellurium-bismuth alloy target, the tellurium target, and the substrate to 100 mm. Close the hatch, and wait for the mechanical pump and molecular pump to pump the vacuum in the chamber to 5×10 -4After the pressure drops below 99.999%, high-purity argon gas with a purity of ≥99.999% is introduced, and a sputtering bias of 800 V is applied, the pulse duty cycle is set to 80%, and the substrate is cleaned for 5 minutes using the ionized argon ions;

[0061] (3) After cleaning, the argon flow rate is set to 90sccm, the working pressure is fixed to 3Pa, the substrate speed is set to 15rpm, the sputtering temperature is set to 25℃, the RF power supply is set to 40W, the DC power supply is set to 10W, the sputtering bias is set to 50V, the pulse duty cycle is set to 80%, the first sputtering is 15 minutes, and the RF and DC power supplies are turned off for 20 minutes after the sputtering is completed. The second sputtering is 15 minutes, and the RF and DC power supplies are turned off for 20 minutes after the sputtering is completed. Repeat the sputtering process for a total of 4 times. The intermittent sputtering method is used to grow the film to prevent the substrate temperature from rising due to continuous sputtering. At the same time, intermittent sputtering can make the atoms on the surface of the film fully relax, which is more conducive to the growth of the film. After the intermittent sputtering is completed, the RF and DC power supplies are turned off, and after maintaining under vacuum conditions for 1 hour, a fiber-feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness is obtained.

[0062] Comparative Example 1

[0063] A method for preparing a bismuth telluride thermoelectric film comprises the following steps:

[0064] (1) Selecting single-side polished silicon oxide wafers and polyimide as substrates, immersing them in water and alcohol and cleaning them with an ultrasonic cleaning machine for 3 times, each time for 5 minutes, and changing the water and alcohol before each cleaning. After cleaning, the substrate surface is dried at 70° C. The substrates are fixed to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then loaded into the sputtering chamber, with the silicon oxide wafer at the center and the polyimide around, the silicon oxide wafer substrate and the polyimide substrate on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 4 mm;

[0065] (2) Fix the tellurium-bismuth alloy target on a DC power supply, fix the tellurium target on an RF power supply, and adjust the distance between the tellurium-bismuth alloy target, the tellurium target, and the substrate to 100 mm. Close the hatch, and wait for the mechanical pump and molecular pump to pump the vacuum in the chamber to 5×10 -4 After the pressure drops below 99.999%, high-purity argon gas with a purity of ≥99.999% is introduced, and a sputtering bias of 800 V is applied, the pulse duty cycle is set to 80%, and the substrate is cleaned for 5 minutes using the ionized argon ions;

[0066] (3) After the cleaning is completed, the argon flow rate is set to 90sccm, the working gas pressure is fixed to 3Pa, the substrate rotation speed is set to 15rpm, the sputtering temperature is set to 25°C, the RF power supply power is set to 40W, the DC power supply power is set to 10W, the sputtering bias is set to 50V, the pulse duty cycle is set to 80%, and the sputtering is continued for 20 minutes. After the continuous sputtering is completed, the RF and DC power supplies are turned off. After maintaining the vacuum condition for 1 hour, a bismuth telluride thermoelectric film is obtained.

[0067] Comparative Example 2

[0068] The method and parameters of this comparative example are the same as those of Example 1, except that in step (3), the sputtering bias voltage is set to 200 V and the pulse duty cycle is set to 80%.

[0069] Example 2

[0070] The method and parameters of this embodiment are the same as those of embodiment 1, except that the sputtering process is repeated a total of 3 times in step (3).

[0071] Example 3

[0072] A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness comprises the following steps:

[0073] (1) Select a single-side polished silicon oxide wafer and polyimide as a substrate, immerse them in water and alcohol, and clean them 4 times with an ultrasonic cleaner, each time for 3 minutes. The water and alcohol need to be replaced before each cleaning. After cleaning, dry the substrate surface at 50° C. Fix the substrate to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then load it into the sputtering chamber, with the silicon oxide wafer at the center and the polyimide around. The silicon oxide wafer substrate and the polyimide substrate are on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 5 mm;

[0074] (2) Fix the tellurium-bismuth alloy target on a DC power supply, fix the tellurium target on an RF power supply, and adjust the distance between the tellurium-bismuth alloy target, the tellurium target, and the substrate to 105 mm. Close the hatch, and wait for the mechanical pump and molecular pump to pump the vacuum in the chamber to 1×10 -4 After the pressure drops below 99.999%, high-purity argon gas with a purity of ≥99.999% is introduced, and a sputtering bias of 850V is applied, the pulse duty cycle is set to 50%, and the substrate is cleaned for 6 minutes using the ionized argon ions;

[0075] (3) After cleaning, the argon flow rate is set to 85sccm, the working pressure is fixed to 3Pa, the substrate speed is set to 10rpm, the sputtering temperature is set to 30℃, the RF power supply is set to 42W, the DC power supply is set to 12W, the sputtering bias is set to 130V, the pulse duty cycle is set to 60%, the first sputtering is 12 minutes, and the RF and DC power supplies are turned off for 10 minutes after the sputtering is completed. The second sputtering is 12 minutes, and the RF and DC power supplies are turned off for 10 minutes after the sputtering is completed. Repeat the sputtering process for a total of 5 times, and use the intermittent sputtering method to grow the film to prevent the continuous sputtering from causing the substrate temperature to rise. At the same time, intermittent sputtering can make the atoms on the surface of the film fully relax, which is more conducive to the growth of the film. After the intermittent sputtering is completed, the RF and DC power supplies are turned off, and after keeping it under vacuum for 1.5 hours, a fiber-feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness is obtained.

[0076] Example 4

[0077] A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness comprises the following steps:

[0078] (1) Select a single-side polished silicon oxide wafer and polyimide as a substrate, immerse them in water and alcohol, and clean them three times with an ultrasonic cleaner, each time for 5 minutes. The water and alcohol must be replaced before each cleaning. After cleaning, dry the substrate surface at 60° C. Fix the substrate to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then load it into the sputtering chamber, with the silicon oxide wafer at the center and the polyimide around. The silicon oxide wafer substrate and the polyimide substrate are on the same horizontal plane, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 2 mm;

[0079] (2) Fix the tellurium-bismuth alloy target on a DC power supply, fix the tellurium target on an RF power supply, and adjust the distance between the tellurium-bismuth alloy target, the tellurium target, and the substrate to 95 mm. Close the hatch, and wait for the mechanical pump and molecular pump to pump the vacuum in the chamber to 3×10 -4 After the pressure drops below Pa, high-purity argon gas with a purity of ≥99.999% is introduced, and a sputtering bias of 750V is applied, the pulse duty cycle is set to 70%, and the substrate is cleaned for 10 minutes using the ionized argon ions;

[0080] (3) After cleaning, the argon flow rate is set to 87sccm, the working pressure is fixed to 2Pa, the substrate speed is set to 20rpm, the sputtering temperature is set to 20℃, the RF power supply is set to 38W, the DC power supply is set to 8W, the sputtering bias is set to 0V, the pulse duty cycle is set to 50%, the first sputtering is 17 minutes, and the RF and DC power supplies are turned off for 30 minutes after the sputtering is completed. The second sputtering is 17 minutes, and the RF and DC power supplies are turned off for 30 minutes after the sputtering is completed. Repeat the sputtering process for a total of 4 times. The intermittent sputtering method is used to grow the film to prevent the substrate temperature from rising due to continuous sputtering. At the same time, intermittent sputtering can make the atoms on the surface of the film fully relax, which is more conducive to the growth of the film. After the intermittent sputtering is completed, the RF and DC power supplies are turned off, and the fiber-feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness is obtained after maintaining it under vacuum conditions for 2 hours.

[0081] Example 5

[0082] The method and parameters of this embodiment are the same as those of embodiment 1, except that in step (3), the sputtering bias voltage is set to 5V and the pulse duty cycle is set to 80%.

[0083] Example 6

[0084] The method and parameters of this embodiment are the same as those of embodiment 1, except that in step (3), the sputtering bias voltage is set to 150 V and the pulse duty cycle is set to 70%.

[0085] from Figure 3 It can be seen that the X-ray diffraction results of all embodiments and comparative examples have the maximum diffraction peak at (015), which indicates that the grown embodiments 1-2 and comparative examples 1-2 are both (015) preferred oriented bismuth telluride thermoelectric films. In addition, a diffraction peak under the (110) orientation was observed in embodiment 1, indicating random stacking of grains. Compared with the (015) orientation, this special film orientation is energetically unfavorable and requires very high density element accumulation during the deposition process, so this orientation is only observed in embodiment 1 with a longer deposition time.

[0086] from Figure 4 It can be seen that the film of Example 2 prepared by the present invention was observed on the surface of the film using a scanning electron microscope. On the surface of the film, the grains are of similar size, evenly distributed, and have no obvious holes, showing the characteristics of high-quality film deposition.

[0087] from Figure 5It can be seen that the feather-like nanocrystalline bismuth telluride thermoelectric films prepared in Example 1 and Example 3 of the present invention are agglomerated by numerous nanocrystals, have a grain size gradient distribution from bottom to top, and have high-density fibrous stacking faults inside the grains. Compared with the traditional single-size columnar, hexagonal spiral and hexagonal grains, the small grains below the feather-like nanocrystals can provide strength, and the large grains above provide the ability of plastic deformation, achieving a synergistic improvement in strength and plasticity.

[0088] from Figure 6 It can be seen that high-density fibrous stacking faults were observed in Example 3 under a high-resolution transmission electron microscope. The fibrous stacking faults further hinder the relative movement of the slip layer by constraining the slip layer, allowing the material to absorb more energy during deformation and showing a better toughening effect. By hindering dislocation movement, stacking faults increase the energy dissipation inside the grains, thereby synergistically enhancing the strength and toughness of the bismuth telluride thermoelectric film.

[0089] By measuring the lattice spacing, it was found that the film was oriented (015), which is consistent with previous X-ray diffraction results.

[0090] from Figure 7 It can be seen that the average grain size of Example 1 is 32.28nm, and the average grain size of Example 2 is 28.82nm, both of which are larger than the average grain size of 20.24nm of Comparative Example 1. According to the "Hall-Petch" effect - the material strength increases with the decrease of grain size, and the theory of mutual exclusion of strength and toughness of materials, that is, materials with high strength have poor toughness, it can be seen that compared with Comparative Example 1, Examples 1 and 2 have better flexibility.

[0091] Figure 8 The experimental process and parameter description: The prepared film was subjected to a uniaxial tensile test using a micro-comprehensive mechanical testing system. The film size was 60 mm × 10 mm and the clamping distance was 20 mm. The change curve of the film resistance during the stretching process was collected through the "it" mode of the electrochemical workstation. The electrode chuck was fixed at both ends of the film, the voltage was constant at 10 V, and the current sensitivity was 10 -3 A. When the film undergoes elastic deformation, the resistance only increases linearly because there is no damage. As the strain increases further, damage will initiate, and the presence of microcracks will significantly increase the resistance, causing the resistance change curve to deviate from the linear stage. Therefore, the strain corresponding to the sudden change in the resistance change rate is the critical strain for crack initiation.

[0092] from Figure 8 It can be seen that Example 1 has a critical strain for crack initiation of up to 7.3%, and Example 2 has a critical strain value of 3.1%, both of which are higher than the critical strain values ​​of Comparative Examples 1-2 by 1.8% and 0.3%, respectively, showing good flexibility, which corresponds to the previous average grain size results.

[0093] Fig. 9 Experimental process and parameter description: The prepared film was subjected to bending cycle test by a homemade bending device. The film size was 60mm×10mm, the clamping distance was 20mm, and the bending radius was fixed at 8mm. The change curve of the film resistance during the bending cycle was collected by the "it" mode of the electrochemical workstation. The electrode chuck was fixed at both ends of the film, the voltage was constant at 10V, and the current sensitivity was 10 -3 A. Using finite element analysis software, the strains on the upper and lower surfaces of the film during the bending cycle were calculated in the elastic buckling analysis mode. During the calculation process, one end of the film was kept fixed and the other end was displaced inward until the bending radius of the film was 8 mm.

[0094] from Fig. 9 It can be seen that the upper surface of the film is stretched and the lower surface is compressed, wherein the maximum strain of the stretch is 1.93% and the maximum strain of the compression is 1.78%. Analysis of the resistance change of the film during the bending cycle shows that the resistance of Example 1 only increases by 20% after bending 10,000 times, and the increase in film resistance when bending 1,000 and 2,000 times is lower than that of other references.

[0095] Fig.10 The experimental process and parameter description: The surface of the film of Example 1 was observed before and after being bent 3000 times under a scanning electron microscope. The scanning voltage was set to 5KV and the magnification was 10000 times.

[0096] from Fig.10 It can be seen that compared with before bending, there is no obvious crack on the film surface of Example 1 after bending 3000 times, showing good ductility.

[0097] Fig.11 The experimental process and parameter description: The relationship between the film conductivity (σ) and temperature (T) was measured using a thermoelectric material testing system. The film was clamped and fixed on the sample stage. One end of the sample stage was fixed at room temperature, and the other end was heated according to the set measurement temperature. The conductivity of the film at different temperatures can be measured by a pair of probes. The measurement temperature range is set to 300K-550K, with a total of 6 measurement temperature points. The data was collected 3 times at each temperature point to take the average value, and the distance between the probes was fixed to 6mm.

[0098] from Fig.11 It can be seen that the conductivity of Example 1 and Comparative Example 1 increases with the increase of temperature. At the same time, the conductivity of Example 1 is always higher than that of Comparative Example 1, showing more excellent electrical properties.

[0099] Fig.12The experimental process and parameter description: The relationship between the power factor (PF) and temperature (T) of the film was measured using a thermoelectric material test system. The film was clamped and fixed on the sample stage. One end of the sample stage was fixed at room temperature, and the other end was heated according to the set measurement temperature. The power factor of the film at different temperatures can be measured by a pair of probes. The measurement temperature range is set to 300K-550K, with a total of 6 measurement temperature points. Data was collected 3 times at each temperature point to take the average value, and the distance between the probes was fixed to 6mm.

[0100] from Fig.12 It can be seen that the power factor of Example 1 increases with the increase of temperature, and the maximum power factor is 2.76μWm at 550K. -1 K -2 .

[0101] from Fig.13 It can be seen that the fiber-rich feather-like nanocrystals can effectively scatter low-frequency phonons without affecting electron transport, that is, they maintain high electrical conductivity while reducing thermal conductivity. According to the calculation formula of ZT value ZT = S 2 σT / κ (S, σ, κ and T represent Seebeck coefficient, electrical conductivity, thermal conductivity and absolute temperature respectively) shows that low thermal conductivity and high electrical conductivity can improve the thermoelectric properties of materials.

[0102] Fig.14 The experimental process and parameter description: Select the Example 1 film after bending 3000 times, attach copper glue to both ends of the film, and connect it to the electrochemical workstation through the electrode chuck to detect the voltage response. That is, when the finger touches the film at room temperature, due to the temperature difference between the body temperature and the environment at both ends of the film, the film can output voltage as a power source.

[0103] from Fig.14 It can be seen that after being bent 3000 times, the film of Example 1 can still stably output a voltage of 1mV by utilizing the temperature difference between body temperature and the environment, and the voltage direction can be adjusted by controlling the contact position between body temperature and the electrode end.

[0104] The present invention is compared with references 1-9 in the background art from four perspectives: preparation method, preparation temperature, microstructure and mechanical properties, as shown in Table 1:

[0105] Table 1 Comparison of preparation methods, parameters and performance of Example 1 and prior art documents 1-9

[0106]

[0107]

[0108] In summary, in terms of preparation process, the present invention adopts the method of magnetron sputtering and co-sputtering to prepare bismuth telluride thermoelectric film in one step at room temperature. Compared with the traditional preparation method, no heating is required during and after the coating process. The preparation process of this work does not require multiple steps, and the preparation of bismuth telluride thermoelectric film can be completed in one step at room temperature. At the same time, compared with single-target sputtering, co-sputtering can better adjust the composition of the prepared film and the sputtering rate of each target material. The preparation method of the present invention is simple and highly operable, which is convenient for large-scale production in the industrial field.

[0109] In terms of structure, the bismuth telluride thermoelectric films prepared by the present invention are all polycrystalline. Since the grain boundaries can effectively prevent crack propagation, they have better toughness and crack propagation resistance than the single crystals prepared by the conventional method. In addition, compared with the traditional single-sized columnar, hexagonal spiral and hexagonal grains, the bismuth telluride thermoelectric films prepared by the present invention are agglomerated by many nanocrystals of different sizes to form feather-like nanocrystals with a gradient grain size from bottom to top, and the grains are rich in high-density fibrous stacking faults.

[0110] In terms of mechanical properties, the critical strain of cracks produced by the bismuth telluride thermoelectric film prepared by the present invention under uniaxial tension reaches ~7.3%, which is close to the critical strain of cracks produced by metal copper film under uniaxial tension ~10%. At a bending radius of 8mm, it can be repeatedly bent more than 10,000 times, which is much greater than the 2,000 times of other films, and the degree of increase in resistivity is comparable to that of other films under 3,000 bends, and the resistivity is only increased by 20% under 10,000 bends, so the bending degree and bending times of the bismuth telluride thermoelectric film prepared by the present invention are higher than those of the bismuth telluride thermoelectric film prepared by the traditional method. This is because according to the fine grain strengthening theory, the grain size below the bismuth telluride thermoelectric film prepared by the present invention is smaller, which can provide strength for the material, and the grain size above the bismuth telluride thermoelectric film is larger, which can provide plastic deformation ability for the material, and achieve a synergistic improvement in strength and plasticity. At the same time, the high-density fibers (stacking faults) grown inside the feather-like grains provide more movable dislocations. The increase in dislocation density leads to more dislocation slip, and the high-density stacking faults have a stronger hindering effect on dislocation slip, which has the effect of strengthening and toughening.

[0111] In terms of thermoelectric performance, when the grain size increases, the reduction in the number of grain boundaries can effectively reduce phonon scattering, while the large number of fibers inside the grains will not reduce electron scattering, which leads to the prepared feather-like bismuth telluride thermoelectric film with nanofibers showing higher conductivity and high power factor at high temperature. The power factor is as high as 2.76μWm at 550K. -1 K -2. In addition, after being bent 3000 times, the fiber feather-shaped nanocrystalline bismuth telluride thermoelectric film prepared by the present invention can still connect electrodes at both ends of the film, and use the temperature difference between body temperature and the environment to stably output a voltage of 1mV, and the voltage direction can be adjusted by controlling the contact position between body temperature and the electrode end. This shows that the fiber feather-shaped nanocrystalline bismuth telluride thermoelectric film prepared by the present invention can meet the needs of body temperature power generation in flexible wearable devices after reasonable series packaging, and has potential commercial prospects.

[0112] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for preparing a fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness, characterized in that: The steps include: (1) Using a silicon oxide wafer and polyimide as a substrate, fixing the substrate to a base plate and then placing it into a sputtering chamber; (2) fixing the tellurium-bismuth alloy target on a direct current power supply, fixing the tellurium target on a radio frequency power supply, adjusting the distances between the tellurium-bismuth alloy target, the tellurium target and the substrate, and cleaning the substrate by an ionization method; (3) After cleaning, an intermittent sputtering method is used to grow a fibrous feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness.

2. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (1), the pretreatment process of the silicon oxide wafer and the polyimide is to select single-sided polished silicon oxide wafer and polyimide as substrates, immerse them in water and alcohol, and then clean them with an ultrasonic cleaner, and dry the substrate surface after cleaning.

3. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (2), the process of cleaning the substrate by ionization method is to introduce argon gas under vacuum conditions, apply sputtering bias, set the pulse duty cycle, and use ionized argon ions to clean the substrate.

4. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (3), the intermittent sputtering method is to set the parameters of argon gas flow rate, working gas pressure, substrate speed, sputtering temperature, RF power supply power, DC power supply power, sputtering bias, and pulse duty cycle, and then sputter for 12 to 17 minutes for the first time, and then turn off the RF and DC power supplies for 10 to 30 minutes after the sputtering is completed. The second sputtering is 12 to 17 minutes, and then turn off the RF and DC power supplies for 10 to 30 minutes after the sputtering is completed, and so on. The sputtering process is repeated a total of 3 to 5 times.

5. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (3), after the intermittent sputtering is completed, the RF and DC power supplies are turned off, and the film is kept under vacuum for 1 to 2 hours to obtain a fibrous feather-like nanocrystalline bismuth telluride thermoelectric film with high toughness.

6. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (2), the distances between the tellurium-bismuth alloy target, the tellurium single substance target and the substrate are all 95 to 105 mm.

7. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 3, characterized in that: In the process of cleaning the substrate by ionization method, the vacuum degree of the vacuum condition is 1×10 -4 Pa~5×10 -4 Pa; the sputtering bias voltage is 750-850V; the pulse duty cycle is set to 50%-80%.

8. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 4, characterized in that: In the intermittent sputtering method, the argon gas flow rate is set to 85-90 sccm, the working gas pressure is fixed to 2-3 Pa, the substrate rotation speed is set to 10-20 rpm, the sputtering temperature is set to 20-30°C, the RF power supply power is set to 38-42 W, the DC power supply power is set to 8-12 W, the sputtering bias is set to 0-150 V, and the pulse duty cycle is set to 50%-80%.

9. The method for preparing the fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness according to claim 1, characterized in that: In step (1), the substrate is fixed to the base plate in the order of first fixing the silicon oxide wafer and then fixing the polyimide, and then loaded into the sputtering chamber, with the silicon oxide wafer in the center and the polyimide around it, and the distance between the outer edge of the silicon oxide wafer substrate and the inner edge of the polyimide substrate is 2 to 5 mm.

10. A fiber-feather-shaped nanocrystalline bismuth telluride thermoelectric film with high toughness, characterized in that: The film is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing hexagonal spiral morphology bismuth telluride thermoelectric thin film

    CN106498354A

  • Method for controlling performance of n-type bismuth telluride film through grain boundary

    CN108447976A

  • Method for preparing bismuth telluride thermoelectric thin film with heterostructure

    CN109554674A

  • Bismuth telluride flexible composite film with porous structure on surface and preparation method of bismuth telluride flexible composite film

    CN113088910A

  • Superhard nano heterogeneous medium-entropy alloy film and preparation method thereof

    CN115595542A